Cloning, expression and characterization of the endoglucanase gene from Bacillus subtilis UMC7 isolated from the gut of the indigenous termite Macrotermes malaccensis in Escherichia coli - Wei, K.S.C.; Teoh, T.C.; Philip, Koshy; Ismail, Salmah; Arifin, Z. (Elsevier, 2015)
Background Bacillus subtilis UMC7 isolated from the gut of termite Macrotermes malaccensis has the ability to secrete a significant amount of extracellular endoglucanase, with an enzyme activity of 0.12 ± 0.01 μmol/min/mL. However, for economically viable industrial applications, the enzyme needs to be expressed in a heterologous host to overcome the low enzyme production from the wild-type strain.